Two faces of the size effect - Guo, Laite (Journal of Banking & Finance, 2023)
This study finds that the size effect has two faces that are predictable from forward-looking signals: conditional on an up signal, small stocks outperform big stocks; conditional on a down signal, big stocks outperform small stocks. Managing size strategies according to the two faces achieves significant performance improvements unexplained by common risk factors. Moreover, the two-faced size effect remains robust to stylized facts that invalidate the unconditional size effect. The conditional performance is consistent with the evidence that the prices of small stocks respond slowly to information shocks and is mainly driven by the conditional difference in cash-flow shocks between small and big stocks. Overall, our findings not only show that both small-minus-big and big-minus-small premiums exist but also highlight the necessity of accounting for these two faces when assessing the size effect.